The Effect of Human Umbilical Cord Mesenchymal Stem Cell on Premature Ovarian Cell Senilism Through miR-10a - Jiang F; Hong J; Jiang J; Li L; Zheng X; Zhao K; Wu X (Dove Medical Press, 2024)
Fan Jiang,1 Jingzhen Hong,1 Juanjuan Jiang,1 Ling Li,1 Xianrui Zheng,1 Kun Zhao,2 Xuebin Wu1 1Reproductive Medicine Center, Zhangzhou Affiliated Hospital of Fujian Medical University, Zhangzhou, 363000, People's Republic of China; 2Fujian Heze Biotechnology Company Limited, Fuzhou, 350000, People's Republic of ChinaCorrespondence: Fan Jiang; Xuebin Wu, Reproductive Medicine Center, Zhangzhou Affiliated Hospital of Fujian Medical University, No. 59, Shengli West Road, Zhangzhou City, Fujian Province, People's Republic of China, Email jiangfan_dr2023@163.com; zzsyywxb@163.comObjective: To investigate the potential protective impact of miR-10a-modified HUMSCs-derived exosomes on both premature ovarian failure and the functionality of ovarian granulosa cells in a POF model.Methods: KGN cells were co-cultured with cisplatin-diaminedichloroplatinum (II) (10 μM) for 24 h to establish an in vitro POF model. The cells were distributed into three distinct groups: the control group, the POF group, and the POF + HUCMSC group. The plasmid sh-NC, sh-miR-10 a and miR-10 a mimic were transfected into KGN cells. After co-cultured with HUCMSC-EVs for 48 h, they were divided into HUCMSC group, sh-miR-10 a-HUMSCs-exosomes group and miR-10 a-HUMSCs-exosomes group. Flow cytometry was adopted to assess the impact of HUMSCs surface immune antigens and miR-10a-HUCMSCs-exosomes on KGN cell apoptosis. Additionally, the evaluation of cell proliferation was carried out through CCK-8 and EDU assays. Western blot analysis was utilized to detect the Caspase-3, Bax, and Bcl-2 proteins levels. Furthermore, the levels of TNF-α, IL-6, IL-10, MDA, SOD, and CAT were quantified using ELISA.Results: Compared with the Control group, the POF group inhibited the growth of ovarian granulosa cells (P< 0.01), reduced the number of EDU cells (P< 0.01), and increased the protein expression of Caspase-3 (P< 0.05) and Bax (P< 0.01). HUMSCs treatment significantly down-regulated the expression of IL-6, TNF-α and MDA, while up-regulating the expression of IL-10, SOD and CAT (P< 0.01); the overexpression of miR-10a promoted cell growth, besides, the introduction of miR-10a-HUMSCs-derived exosomes led to an elevation in the proliferation rate of OGCs affected by POF and concurrently suppressed the apoptosis rate.Conclusion: HUMSCs-derived exosomes modified by miR-10a have protective effects on premature ovarian failure and ovarian granulosa cell function in POF model.Keywords: miR-10a, premature ovarian failure, hUMSCs, cis-diaminedichloroplatinum, ovarian granulosa cells